Analisis Yuridis Pembuktian Sederhana dan Force Majeure dalam Penundaan Kewajiban Pembayaran Utang - Mulyana, Marga; Sudawan, Moh. Yuda (Neolectura, 2025)
Penundaan Kewajiban Pembayaran Utang (PKPU) is a legal mechanism that aims to provide an opportunity for debtors to restructure their debts to avoid bankruptcy. One of the important elements in the PKPU process is the application of the principle of simple proof as stipulated in Pasal 8 ayat (4) Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan PKPU. However, the application of this principle often faces challenges, especially in cases involving force majeure arguments. This research aims to examine the application of simple proof in PKPU practice, as well as identify the impact of force majeure arguments on court decisions Through the analysis of several commercial court decisions, including Decision Number 2/Pdt.Sus-PKPU/2024/PN Niaga Jkt.Pst, Decision Number 51/Pdt.Sus-PKPU/2024/PN Niaga Jkt.Pst, and Decision Number 180/Pdt.Sus- PKPU/2024/PN Niaga Jkt.Pst, this research shows that although the argument of force majeure is often raised by debtors as an excuse for inability to pay debts, the courts favour objective evidence showing the existence of overdue debts, This research also emphasises the importance of caution in the application of simple proof, especially in cases with high legal complexity, such as those involving disputed objects with diverse property rights. Based on these findings, this study provides recommendations to improve regulations related to simple proof and strengthen the courts' understanding of its application in PKPU cases.